2021
DOI: 10.1111/epi.16916
|View full text |Cite
|
Sign up to set email alerts
|

Early onset epilepsy and sudden unexpected death in epilepsy with cardiac arrhythmia in mice carrying the early infantile epileptic encephalopathy 47 gain‐of‐function FHF1(FGF12) missense mutation

Abstract: Objective: Fibroblast growth factor homologous factors (FHFs) are brain and cardiac sodium channel-binding proteins that modulate channel density and inactivation gating. A recurrent de novo gain-of-function missense mutation in the FHF1(FGF12) gene (p.Arg52His) is associated with early infantile epileptic encephalopathy 47 (EIEE47; Online Mendelian Inheritance in Man database 617166). To determine whether the FHF1 missense mutation is sufficient to cause EIEE and to establish an animal model for EIEE47, we so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…FHFs are pleiotropic proteins whose dysregulation is associated with disorders of the nervous system, cardiac diseases and cancer [ 19 , 39 53 ]. The specificity of FHFs function appears to be largely determined by their subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…FHFs are pleiotropic proteins whose dysregulation is associated with disorders of the nervous system, cardiac diseases and cancer [ 19 , 39 53 ]. The specificity of FHFs function appears to be largely determined by their subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the FGF12 mouse variant model fgf12 R52H/+ which suffers from spontaneous seizures and dies of sudden unexplained death in epilepsy (SUDEP) at around 16 days of age. 31 Veliskova and co-workers treated these mice with phenytoin, but the survival time was just marginally prolonged to about 19 days. 31 Another previous study showed the modifying effect of a hypomorphic variant in GABRA2 which increased seizure severity in mouse models carrying human SCN8A variants.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Veliskova and co-workers treated these mice with phenytoin, but the survival time was just marginally prolonged to about 19 days. 31 Another previous study showed the modifying effect of a hypomorphic variant in GABRA2 which increased seizure severity in mouse models carrying human SCN8A variants. This suggests that GABRA2 could be a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were video recorded for offline analysis of the incidence of S-IRA, latency to AGSZs, duration of wild running, clonic seizures, tonic-clonic seizures, and seizure scores, as described previously. 35 , 36 , 37 To observe the incidence of death among DBA/1 mice as well as heart rate changes due to esmolol, the group of mice (n = 6) used to confirm S-IRA 24 h before the start of the experiment was pre-treated with esmolol (50 mg/kg, IP) without administration of atomoxetine and subjected to acoustic stimulation in the same manner. For DBA/1 mice in all of the different pre-treatment groups, ECG was performed before acoustic stimulation and after S-IRA.…”
Section: Methodsmentioning
confidence: 99%
“…The mice were video recorded for offline analysis of the incidence of S-IRA, latency to GSZs, duration of wild running, clonic seizures, tonic-clonic seizures, and seizure scores, as described previously. 35 , 36 , 37 For DBA/1 mice in all the different pre-treatment groups, ECG was performed before and after IP administration of PTZ.…”
Section: Methodsmentioning
confidence: 99%